Abdominal versus vaginal hysterectomy: Appraisal of indications and complications in a Nigerian Federal Medical Centre - Umeora, OUJ; Onoh, RC; Eze, JN; Igberase, GO (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aims: To compare hysterectomies performed via the abdominal and vaginal routes in terms of indications and associated complications. Methods: Review of retrospective data on all cases of hysterectomies performed at the Federal Medical Centre Abakaliki over a six-year period (January 2000 to December 2005). Results: There were a total of 62 hysterectomies. Of these, 33 (52.2%) were abdominal hysterectomies while 29 (46. 8%) were vaginal hysterectomies. Hysterectomy was carried out predominantly for grand multiparous women [21 (72.4%) and 21 (63.7%) were abdominal and vaginal hysterectomies respectively]. The mean ages of the patients were 48.8 years and 55.5 years for the abdominal and vaginal operations respectively. The only indication for vaginal hysterectomy in this study was uterovaginal prolapse while uterine fibroid was the commonest indication for abdominal hysterectomy. Complications and duration of hospital stay were more following abdominal hysterectomy. Conclusion: There is need for training and retraining of specialist gynaecologists and trainee residents on procedures of hysterectomies, especially vaginal hysterectomy to expand the indications for the vaginal surgery which is attended with less postoperative morbidity. Key words: indications; complications; route; pyrexia; wound; Abakaliki DOI: 10.3126/njog.v4i1.3328 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 25-29